Cricket Paralysis Virus Threatens Cricket Farm Business - Piper, Savannah; Marshall, Jeremy; Nouri, Shahideh (My University, 2018)
Crickets are a vital source of protein for many human and animals such as frogs, geckos, lizards and are starting to make a debut as an ingredient in dog food. When crickets are consumed it is vital the crickets are free of disease (Dunn). One disease that crickets are susceptible to is the cricket paralysis virus. Cricket paralysis virus (CPV) can “infect several insect orders such as Diptera, Lepidoptera, Orthoptera, Hemiptera and Hymenoptera, as well as a diverse range of cultured insect cells”(King). The cricket paralysis virus belongs to the family of viruses classified as Dicistroviridae. Dicistroviridae viruses can be characterized as “small enveloped viruses with monopartite, linear, and positive sense RNA genomes”(Valles). A collection of cricket samples from a cricket farm was sent to the lab to be tested for the cricket paralysis virus. If the crickets test positive for the cricket paralysis virus then the cricket farm may be forced to shut down. However, the results of the experiment were negative for the virus. These results are crucial because they impact the people or animals that consume these crickets, the fate of the business that produces the crickets, and contributes to more experiments related to the cricket paralysis virus.
Keywords: Fall 2018